The Masquelet technique in traumatic loss of the talus after open lateral subtalar dislocation—A case report. (2019) - Abdulazim, Ahmed Nabil; Reitmaier, Martina; Eckardt, Henrik; Osinga, Rik; Saxer, Franziska
Highlights: The Masquelet technique is suitable for emergency treatment and later reconstruction. The Masquelet technique is an option even in presence of contamination and vascular impairment. In case of traumatic bone loss, the Masquelet technique can preserve leg length not only in long-bone defects. For grafting procedures the Masquelet technique can improve the viability at the recipient site. The biologic activity of the Masquelet membrane facilitate union at challenging graft-sites. Abstract: Introduction: Subtalar dislocations are rare injuries and treatment recommendations missing. Gross contamination and devascularisation are aspects supporting talectomy as potential treatment choice. Reconstruction in these cases can be challenging. The Masquelet technique presents one viable option. Presentation of case: A carpenter sustained a high energy chrush injury with traumatic open lateral talar dislocation qualifying as Gustillo Anderson type IIIc injury, a mangeled extremity index of 7 and gross contamination. The severity of soft tissue damage and contamination prompted the decision for talectomy before plastic coverage with a gracilis flap. Additionally a Masquelet procedure with cement spacer was initiated. After consolidation of the soft tissues a hindfoot arthrodesis with approximate preservation of leg length could be performed. In the course of treatment, the patient suffered no infection and could resume full weight bearing after nine months. The patient resumed his previous occupation with adapted workload and is satisfied with the treatment result. Discussion: In the present case the principle options were talus preservation or talectomy with reconstruction. Talus preservation in the presence of gross contamination can be associated with the risk of infection, in addition there is a risk to develop secondary arthritis. For this individual patient the a fast and definite solution was important at this point in life. Surgeons therefore opted for talectomy. To optimally reconstruct leg length and optimize for arthrodesis the Masquelet technique was employed. Conclusion: The Masquelet technique is a viable option also in the emergency situation to preserve extremity length and optimize tissue viability.